DEVELOPMENT AND IMPLEMENTATION OF THE PEDAGOGICAL SYSTEM OF FORMATION OF ECOLOGICAL COMPETENCY OF FUTURE TEACHERS OF NATURAL sciences IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATION INSTITUTIONS - Siaska, Inna (European Science, 2022)
The problem of formation of ecological competency of applicants for higher pedagogical education requires a comprehensive and systematic approach to its solution. To this end, a pedagogical system has been developed that reflects all pedagogical laws and